Due inediti rotoli pergamenacei. L'Ordine Teutonico e la sua organizzazione archivistica al principio del XIV secolo - Bombi, Barbara (Scrineum, 2013)
After a brief overwiew on the archival history of the Teutonic Order in the thirteenth and early fourteenth century, the article focuses on the problem of conservation practices and record keeping that the Order adopted during the period of displacement and reorganization of its archives. Two parchment rolls are analyzed, both preserved in the Geheimes Staatsarchiv Preussischer Kulturbesitz in Berlin and containing headings of mostly papal documents issued in favor of the Order in the thirteenth century. The first roll was drawn up at the beginning of the fourteenth century on the documents preserved in the Roman church of Santa Maria in Domnica: the roll is one of the last witnesses of the size of the Roman archive of the Order before its dispersion. The second roll was commissioned in 1318 by the procurator generalis of the Order in the Avignon Curia and was compiled to affirm, first of all, the lawsuit of the Teutonic Knights on rights in Livonia against the archbishop of Riga. The authors of this second roll used, in all probability, compilations made by the will of procuratores of the Order at the Papal Curia ​​in the thirteenth century and based on registers of Papal Chancery.